Giuseppe Verdi, a theatrical vision of the voice in the opera Macbeth (2009)
This paper analyzes the contributions of Giuseppe Verdi to the Italian melodramatic opera. The study of the Macbeth opera has been carried out through the score and the correspondence between Verdi and his collaborators and performers and aims to highligh